The Components of Arguments on the Friday Sermon in the City of Makassar - Saputra, Dedi Gunawan; Judijanto, Loso; Amir, Andi Subhan; Zubairi, Ahmad (OKARA: Jurnal Bahasa dan Sastra, 2024)
Global issues related to Friday sermons include the potential spread of radical ideology, extremism, and discriminatory messages, which can contribute to social inequality and conflict. Additionally, the lack of education and awareness in sermons may affect the understanding of religious teachings and global issues, leading to knowledge gaps and social divisions. Despite these concerns, few studies have specifically analyzed the components of arguments used in Friday sermons in the City. This study aims to describe the components of arguments in Friday sermons in Makassar City. The method used in this research uses qualitative research methods in the form of discourse analysis methods carried out in 5 districts, namely Bontoala, Mamajang, Panakkukang, Rappocini, and Tamalate in Makassar City. A purposive sampling technique was used to obtain a sample of 15 respondents. The data collection technique was done by recording the sermon directly. The results showed six components used to construct arguments in Friday sermons in Makassar, including claim, data, warrant, backing, modal qualifier, and rebuttal. The study's results are expected to improve the ability of the preachers in charge of Friday prayers to utilize various argument components in each sermon delivered. In addition, using components with creative techniques is important to attract the attention of the Friday congregation.